Network management in distributed systems - Abawajy, Jemal H.; Pathan, Mukaddim; Pathan, Al-Sakib Khan; Rahman, Mustafizur (West University of Timisoara, Romania, 2010)
The emergence of Web as a ubiquitous platform for innovations has laid the foundation for the rapid growth of the Internet and emerging distributed computing platforms. Other than being a great source of fun and enjoyment, hundreds and thousands of people around the world rely on these systems for various tasks related to their livelihoods. The overwhelming growth of Internet and its users is a reality, which has put new thoughts among the research community to devise new ideas for giving coverage to a huge number of people around the globe. Side-by-side, the use of mobile and wireless devices such as PDA, laptop, and cell phones for accessing the distributed systems has paved the ways for related distributed computing technologies to flourish through recent developments. However, the increasing scale, complexity, heterogeneity, and dynamism of Internet and distributed computing systems with respect to communication networks, resources and applications have made such systems brittle, unmanageable and insecure. This scenario calls for innovative solutions to deal with the complexity, dynamism, heterogeneity, and uncertainty of distributed systems and provide a holistic approach for the development of systems that can meet the requirements of performance, fault tolerance, reliability, security, and Quality of Service (QoS). As of today, numerous applications depend on distributed computing and networking infrastructures to operate. The management of these functionally and geographically distributed infrastructures is crucial to ensure effective operation of applications. This special issue aims at compiling the recent advancements as well as some basic issues in the fields of network management in distributed computing and Internet-based systems....